Economic-social stratification between extravagance and harmony - Emilian Merce; Manea Drăghici; Cristian Călin Merce (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The work highlights the fact that the ordering of individual values is supported by the act of Divine creation. The Star of David is the source of inspiration and action strategy for achieving an optimal structure of human society based on cooperation. The hexagon in the Star of David is an ancient symbol that points directly to high concepts and valences, with magical force and special energy charge. The powerful energy of this symbol - associated with perfection, peace, tranquility, fulfillment and eternity - generates a special state of well-being, a balance between the physical body and the spirit, a harmony between the outside and the inside. Deciphering the meaning of the Hexagon of Harmony represents the path to the pure consciousness of good. Recognizing the meaning of such a symbol, man becomes aware and discovers his role in the great universe and on earth. We worship, by relating to the Hexagon of harmony, the great and the small universe and become aware of the finite and infinite limits of our destiny. The Star of David symbol instills in us the strength and wisdom of the hexagon, being in sacred geometry one of the most powerful, fascinating and beneficial symbols. Both the rich and those who populate the base of the social pyramid can campaign for the elimination of excesses using the sources of the Hexagon of harmony as a source of shaping the spirit. This also taking into account the context of the abusive realities faced by the contemporary social system. "And what is chosen of the poor"? Foreign support can be helpful, but, like fortune falling from the sky, it can also harm. It can discourage effort and instill a crippling sense of incapacity. According to the African proverb, "The hand that receives is always below the hand that gives"(Havinden and Meredith,2013).
Keywords: Z13; J16; J28; 330; Star of David; social pyramid; earnings pyramid; social harmony